PENINGKATAN KEMAMPUAN BERBAHASA EKSPRESIF MELALUI KEGIATAN BERCERITA DENGAN MEDIA MONTASE PADA ANAK KELOMPOK B DI BA AISYIYAH II JAMALAN TONGGALAN KLATEN - Siti Solichah; Setyoadi Purwanto (QURROTI, 2022)
The background of the research problem is that the expressive language skills of Group B BA 'Aisyiyah II Jamalan Klaten are low. This is evidenced by the results in carrying out storytelling activities, out of 21 students only 1 student received a BSH score on the indicator of expressive language skills so that the competencies that were the target of learning could not be achieved. The aims of this study were: 1. To find out how the implementation of learning to improve expressive language skills with montage media for group B children at BA 'Aisyiyah II Jamalan Klaten. 2. To find out the increase in children's expressive language skills after the use of group B montage media at BA 'aisyiyah II Jamalan Klaten. The research method used is descriptive qualitative in the form of Classroom Action Research (CAR). The results showed that the implementation of learning to improve expressive language skills in group B at BA 'Aisyiyah II Jamalan Klaten, was carried out through the stages of conditioning, media preparation and introduction, demonstrations, group division, storytelling practice with montage, and ended with closing. Improvement of Expressive Language Ability after the use of group B montage media at BA 'Aisyiyah II Jamalan Klaten, obtained; Pre cycle 25%, Cycle I 72.3%, Cycle II 93.65%, so that the increase is 68.65%.